In Vitro Characterization of Reversine-Treated Gingival Fibroblasts and Their Safety Evaluation after In Vivo Transplantation - Carlos Miguel Marto; Mafalda Laranjo; Ana Cristina Gonçalves; Anabela Paula; Joana Jorge; Rui Caetano-Oliveira; Maria Inês Sousa; Bárbara Oliveiros; João Ramalho-Santos; Ana Bela Sarmento-Ribeiro; Manuel Marques-Ferreira; António Cabrita; et al. (MDPI AG, 2024)
Reversine is a purine derivative that has been investigated with regard to its biological effects, such as its anticancer properties and, mostly, its ability to induce the dedifferentiation of adult cells, increasing their plasticity. The obtained dedifferentiated cells have a high potential for use in regenerative procedures, such as regenerative dentistry (RD). Instead of replacing the lost or damaged oral tissues with synthetic materials, RD uses stem cells combined with matrices and an appropriate microenvironment to achieve tissue regeneration. However, the currently available stem cell sources present limitations, thus restricting the potential of RD. Based on this problem, new sources of stem cells are fundamental. This work aims to characterize mouse gingival fibroblasts (GFs) after dedifferentiation with reversine. Different administration protocols were tested, and the cells obtained were evaluated regarding their cell metabolism, protein and DNA contents, cell cycle changes, morphology, cell death, genotoxicity, and acquisition of stem cell characteristics. Additionally, their teratoma potential was evaluated after in vivo transplantation. Reversine caused toxicity at higher concentrations, with decreased cell metabolic activity and protein content. The cells obtained displayed polyploidy, a cycle arrest in the G2/M phase, and showed an enlarged size. Additionally, apoptosis and genotoxicity were found at higher reversine concentrations. A subpopulation of the GFs possessed stem properties, as supported by the increased expression of CD90, CD105, and TERT, the existence of a CD106+ population, and their trilineage differentiation capacity. The dedifferentiated cells did not induce teratoma formation. The extensive characterization performed shows that significant functional, morphological, and genetic changes occur during the dedifferentiation process. The dedifferentiated cells have some stem-like characteristics, which are of interest for RD.